Molecular cytogenetic characterization of Xp22.32→pter deletion and Xq26.3→qter duplication in a male fetus associated with 46,Y,rec(X)dup(Xq) inv(X)(p22.3q26.3), a hypoplastic left heart, short stature, and maternal X chromosome pericentric inversion - Chih-Ping Chen; Chen-Yu Chen; Schu-Rern Chern; Peih-Shan Wu; Yen-Ni Chen; Shin-Wen Chen; Chen-Chi Lee; Dai-Dyi Town; Meng-Shan Lee; Chien-Wen Yang; Wayseen Wang (Elsevier, 2016)
Objective: We present molecular cytogenetic characterization of an Xp22.32→pter deletion and an Xq26.3→qter duplication in a male fetus with congenital malformations and maternal X chromosome pericentric inversion. Materials and Methods: A 22-year-old woman underwent amniocentesis at 17 weeks of gestation because of an abnormal maternal serum screening result. Prenatal ultrasound revealed a hypoplastic left heart and short limbs. Amniocentesis revealed a karyotype of 46,Y,der(X) t(X;?)(p22.31;?). The pregnancy was subsequently terminated, and a malformed fetus was delivered with short stature and facial dysmorphism. Repeat amniocentesis was performed before termination of the pregnancy. Array comparative genomic hybridization was performed on uncultured amniocytes and maternal blood. Conventional cytogenetic analysis was performed on cultured amniocytes, cord blood, and blood from both parents. Fluorescence in situ hybridization was performed on cultured amniocytes. Results: The maternal karyotype was 46,X,inv(X)(p22.3q26.3). The fetal karyotype was 46,Y, rec(X)dup(Xq)inv(X)(p22.3q26.3) or 46,Y, rec(X)(qter→q26.3::p22.3→qter). Array comparative genomic hybridization on uncultured amniocytes revealed a 4.56-Mb deletion of Xp22.33-p22.32 encompassing SHOX, CSF2RA, and ARSE, and a 19.22-Mb duplication of Xq26.3-q28 encompassing SOX3, FMR1, MECP2, RAB39B, and CLIC2 in the fetus. The mother did not have X chromosome imbalance. Conclusion: Detection of X chromosome aberration in a male fetus should give suspicion of a recombinant X chromosome derived from maternal X chromosome pericentric inversion.